2017
DOI: 10.2337/dc18-s008
|View full text |Cite
|
Sign up to set email alerts
|

8. Pharmacologic Approaches to Glycemic Treatment: Standards of Medical Care in Diabetes—2018

Abstract: The American Diabetes Association (ADA) “Standards of Medical Care in Diabetes” includes ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
318
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(327 citation statements)
references
References 60 publications
2
318
1
6
Order By: Relevance
“…However, some studies have reported that intensive glycemic control may not be enough to stop rapid deterioration in renal function in late CKD [30]. Our diabetic patients had good control of glucose that glycated hemoglobin level was under the recommendation value by American Diabetes Association (ADA) [31]. Therefore, we performed subgroup analysis to examine the effect of glycated hemoglobin on the association between serum Angpt2 and adverse renal outcomes in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported that intensive glycemic control may not be enough to stop rapid deterioration in renal function in late CKD [30]. Our diabetic patients had good control of glucose that glycated hemoglobin level was under the recommendation value by American Diabetes Association (ADA) [31]. Therefore, we performed subgroup analysis to examine the effect of glycated hemoglobin on the association between serum Angpt2 and adverse renal outcomes in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…There was lower use of metformin in older adult visits, particularly for those individuals aged 75 years or older, likely due in part to a higher prevalence of chronic kidney disease among older adults, which is the major contraindication to metformin use. 8,29,30 In 2016, the US Food and Drug Administration adopted less restrictive guidelines on the use of metformin in chronic kidney disease. 31 Future studies should examine the impact of this change.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that GLP-1 receptor agonists are less desirable for older patients due to their side-effect profile or injectable mode of administration. 8,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 - 7 For this reason, these should be the drugs of choice to be used in combination with metformin in patients with established cardiovascular diseases according to the American Diabetes Association recommendations. 8 Nevertheless, few studies have been conducted on patients with recently diagnosed diabetes and low prevalence of cardiovascular diseases.…”
mentioning
confidence: 99%